Pengaruh Lokasi, Harga Dan Promosi Terhadap Keputusan Pembelian Kavling Puri Amartya Pandaan - Rizqi, Moch Ilham Khoirur; Rizal, Mohammad; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to examine the influence of location, price, and promotion on the decision to purchase plots in Puri Amartya Pandaan. The population in this study is all customers of Puri Amartya Pandaan plots. The sample in this study was a saturated sample with a sample of 66 respondents. The research method in this study uses quantitative research. Based on testing using simultaneous Test F analysis, the results showed a significant influence between variable X (Location, Price, and Promotion) simultaneously on variable Y (Purchase Decision) on customers of Puri Amartya Pandaan plot. Partial Test Analysis shows that location, price, and promotion variables each have a positive and significant effect on the decision to purchase plots in Puri Amartya Pandaan. Keywords: Location, Price, Promotion, Purchase Decision